A família no romance "Vida e morte de M. J. Gonzaga de Sá" - Ribeiro, Francisco Washington Moreira (2012)
This study tries to follow the meanings that the family takes in the novel Vida e morte de M. J. Gonzaga de Sá, by Lima Barreto. In the narrative the subjectivity of the characters raises questions about the worth of the family institution during times of bourgeois changes in the Brazilian history, the First Republic. The assessment concerning the family also precedes the republican moment, because the novel goes to the past to observe family relationships as tradition. We admit the historical matters that get into the plot, in the other words, we respect the autonomy of the literary text. It means that the literary judgment leads to the social considerations instead of the opposite attitude, therefore, the sociological arguments have aesthetic worth. In conclusion, Lima Barreto’s book suspects the bourgeois family, refused as a microsystem that risks the intellectual and critical independence of the characters. However, Vida e morte also moves the Brazilian paternalistic inheritance and the difficulties faced when the person stays away from the family. Hence, the novel makes the discussions about the family in meeting between past and present, satire and appreciation, refusal and approach related to this social organization.